Contemporary dynamics of human mobility: a systematized review - Roman-Acosta, Daniel; Depablos-Machado, Lusby; Buelvas-Sierra, Ramón Benjamín; Roman-Acosta, Daniel; Depablos-Machado, Lusby; Buelvas-Sierra, Ramón Benjamín; Roman-Acosta, Daniel; Depablos-Machado, Lusby; Buelvas-Sierra, Ramón Benjamín (Corporación Universitaria Americana, 2024)
Introduction: In the interwoven fabric of contemporary human mobility and the use of information and communication technologies, this article addresses fundamental concerns such as privacy and government control of biometric data in the migration sphere; Objective: To analyze the ethical, legal and social implications of digital tools in migration, emphasizing challenges and opportunities, especially in relation to privacy and AI-driven decision-making; Methodology: Adopting a qualitative approach with a documentary and descriptive methodology, a systematic literature review was carried out, following some of the PRISMA guidelines, to explore the intersection between technology and migration from various perspectives; Results: Ethical challenges are revealed in migrant health, risks in AI decision-making, legal challenges of biometric surveillance and privacy concerns in digital migration; Conclusions: The need to ethically frame the use of digital tools is highlighted, ensuring the privacy and rights of migrants, and fostering genuine collaboration to support them in their migration experience.